1996
DOI: 10.1037/0021-843x.105.2.166
|View full text |Cite
|
Sign up to set email alerts
|

Escalated substance use: A longitudinal grouping analysis from early to middle adolescence.

Abstract: The authors surveyed a cohort of 1,184 adolescents in the 7th, 8th, and 9th grades. Measures of tobacco, alcohol, and marijuana use and of constructs from 3 theoretical models of substance use were obtained at each point. Clustering analysis for 3-wave substance use data indicated subgroups of nonusers, minimal experimenters, late starters, and escalators. Discriminant function analyses tested whether study variables differentiated the subgroups. One discriminant function accounted for the majority of between-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
178
1
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(201 citation statements)
references
References 46 publications
16
178
1
6
Order By: Relevance
“…Estos resultados son consistentes con numerosos estudios que han demostrado que el estrés vital predice el consumo de drogas en adolescentes. En particular, los acontecimientos vitales negativos se han asociado al consumo de tabaco (Wills et al, 1996), alcohol (Wills, 1986;Windle y Windle, 1996) y otras drogas (Arellanez-Hernández et al, 2004;Biafora, Warheit, Vega y Gil, 1994;Unger et al, 2001). Windle y Windle (1996), además, encontraron que esta asociación puede ser diferente dependiendo de la magnitud y naturaleza de los acontecimientos estresantes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estos resultados son consistentes con numerosos estudios que han demostrado que el estrés vital predice el consumo de drogas en adolescentes. En particular, los acontecimientos vitales negativos se han asociado al consumo de tabaco (Wills et al, 1996), alcohol (Wills, 1986;Windle y Windle, 1996) y otras drogas (Arellanez-Hernández et al, 2004;Biafora, Warheit, Vega y Gil, 1994;Unger et al, 2001). Windle y Windle (1996), además, encontraron que esta asociación puede ser diferente dependiendo de la magnitud y naturaleza de los acontecimientos estresantes.…”
Section: Discussionunclassified
“…Como consecuencia, a menudo se experimenta depresión y otras emociones negativas. Esto ha llevado a sugerir que el consumo de alcohol y tabaco (Wills, 1986;Wills, McNamara, Vaccaro y Hirky, 1996) y de otras drogas (ArellanezHernández, Díaz, Wagner-Echeagaray y Pérez, 2004;Griffin, Séller, Botvin y Díaz, 2001) podrían representar intentos disfuncionales de manejo de estas dificultades de adaptación. Es por ello que se ha asociado el estrés vital como factor de riesgo para el consumo de drogas en adolescentes (Wills, 1986;Windle y Windle, 1996).…”
unclassified
“…Human psychostimulant abusers show a higher degree of morbidity than the general population (Cregler 1989), and the results of the present study suggest that alterations in the activity of the HPA axis in response to stress might be one factor responsible for this effect. Many human drug addicts who abuse psychostimulants also exhibit an increased reactivity to stress (Keller and Wilson 1994;Wills et al 1996), which is often self-medicated through further substance abuse (Markou et al 1998). Animal models of drug addiction have demonstrated that stress can be an important factor in determining the amount of drug that is consumed, as well as increasing the probability of acquiring drug self-administration and relapsing during extinction (Haney et al 1995;Erb et al 1996;Tidey and Miczek 1997).…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the number of statistical tests, we based the primary analysis on the composite substance use score, but we also performed analyses for each of the substance use indices. Because Strawbridge et al (1998) suggested that buffering interactions 1 The study included other measures, such as parental support and adolescent coping (see Wills, McNamara, Vaccaro, & Hirky, 1996), which are beyond the scope of the present article.…”
Section: Test For Buffering Effectsmentioning
confidence: 99%